2023
DOI: 10.7759/cureus.51099
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Virtual Reality in Controlling Pain and Anxiety Levels in Four-to-Six-Year-Old Children During Dental Treatment

Omar S Almajed,
Rakan Alhujhuj,
Eyad Alshaheen
et al.

Abstract: Background and objective Oral health is critical for children's overall well-being; however, dental anxiety often leads to the avoidance of necessary dental care among children. Virtual reality (VR) has emerged as a successful adjunctive tool in various clinical settings, including pain management. This cohort study explores the use of VR technology in reducing anxiety and pain perception during dental procedures for children. The primary objective of this study was to assess the efficacy of VR dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Dental anxiety, or DA, is more common among young children and adolescents and encompasses physical, cognitive, and emotional aspects. It is characterized by a fear of past negative experiences during hospital visits typically affecting 5-20% of populations, and usually tends to diminish with age [16]. Previous research studies including both adults and children with developmental challenges have demonstrated the beneficial effects of multisensory environment (MSE) or SADE on mental states [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Dental anxiety, or DA, is more common among young children and adolescents and encompasses physical, cognitive, and emotional aspects. It is characterized by a fear of past negative experiences during hospital visits typically affecting 5-20% of populations, and usually tends to diminish with age [16]. Previous research studies including both adults and children with developmental challenges have demonstrated the beneficial effects of multisensory environment (MSE) or SADE on mental states [17,18].…”
Section: Discussionmentioning
confidence: 99%